New trans–β–bergamotene derivatives in the root and the flower essential oils of Cyanthillium cinereum (L.) H. Rob. from Côte d'Ivoire. Issue 19 (2nd October 2019) - Boué, Guy Blanchard; Boti, Jean Brice; Tonzibo, Zanahi Félix; Paoli, Mathieu; Bighelli, Ange
Abstract: Root and flower essential oils of Cyanthillium cinereum (L.) H. Rob. (Synonym Vernonia cinerea (L.) Less.) (Asteraceae) collected in Southern Côte d'Ivoire was investigated using a combination of chromatographic and spectroscopic techniques. The root oil composition was dominated by trans –β–bergamotene (20.7%), β–elemene (19.0%), cyperene (10.6%), germacrene A (7.1%) and β–pinene (3.8%), whereas γ–humulene (31.0%), ( E )–β–caryophyllene (17.0%), trans –β–bergamotene (7.7%), β–pinene (7.5%) and ( E )–β–farnesene (6.0%) were the major components of flower oil. Two new compounds bearing the trans –β–bergamotene framework were identified: trans –β–bergamotenone and ( E )– trans –β–bergamotenol. Graphical Abstract: